An adult case of congenital duodenal diaphragm that was successfully treated by endoscopic resection using a grasping‐type scissor forceps. Issue 1 (2nd February 2022) - Fukuda, Shin‐ichiro; Ichida, Kaoru; Kitagawa, Yusuke; Nakano, Kayoko; Tomohito, Chaen; Yoshimura, Daisuke; Ochiai, Toshiaki; Ihara, Eikichi; Ogawa, Yoshihiro
Abstract: Congenital duodenal diaphragm (CDD) is a rare disease that is usually diagnosed in the neonatal period; however, it is sometimes diagnosed later in the adult period. A 39‐year‐old woman was referred to our hospital due to tarry stool and anemia. Emergent esophagogastroduodenoscopy (EGD) revealed an obstructing membranous structure with a small orifice in the second portion of the duodenum, together with dilatation of the bulbar part. The membranous structure was accompanied by a Dieulafoy‐like vessel on the backside, which was considered to have caused tarry stool and anemia. The Dieulafoy‐like vessel was successfully treated by endoscopic hemostasis. Based on the computed tomographic gastrography and barium duodenography findings, it was diagnosed as CDD. Later, endoscopic resection of the diaphragm was conducted by an endoscopic submucosal dissection (ESD)‐based procedure, with the use of an electrosurgical grasping‐type scissor forceps (ClutchCutter [CC]). There were no procedure‐related complications. The definite diagnosis of CDD was made based on the observation of typical structures in a pathological examination. This is the first case report of adult CDD that was successfully treated by endoscopic resection using ESD‐based techniques with a CC.